Reproductive Endocrine Health in Pubertal Females with Epilepsy on Antiepileptic Drugs: Time to Screen? - Rauchenzauner, Markus; Roscia, Sarah; Prieschl, Manuela; Wildt, Ludwig; Haberlandt, Edda; Baumann, Matthias; Rostasy, Kevin; Agostinelli, Sergio; Pizzolorusso, Antonella; Luef, Gerhard; Verrotti, Alberto (Neuropediatrics, 2014)
Objectives Although previous studies suggest that valproate (VPA) may induce reproductive endocrine disorders, the effects of newer antiepileptic drugs (AEDs) on reproductive endocrine health have not been widely investigated and compared with those of older AEDs. Therefore, this multicenter cross-sectional study aimed to evaluate the prevalence of reproductive endocrine dysfunctions in pubertal females with epilepsy receiving VPA, lamotrigine (LTG), or levetiracetam (LEV) monotherapy.Patients and Methods Pubertal girls on VPA (n = 11), LTG (n = 8), or LEV (n = 13) monotherapy for at least 6 months were recruited. Healthy sex-matched and age-matched subjects were enrolled as controls (n = 32). Each participant underwent a comprehensive physical examination concerning signs of hyperandrogenism. The Ferriman–Gallwey score of hirsutism was assessed. In addition, all patients completed a standardized questionnaire regarding epilepsy, menstrual cycle, and hirsutism features. Adiposity indices were measured and weight gain was documented for each subject.Results Hirsutism score, occurrence of hyperandrogenism features, and adiposity indices were significantly higher in the VPA group when compared with LEV and control groups. VPA therapy was more frequently associated with weight gain when compared with LTG and controls, whereas no significant differences with regard to signs of hyperandrogenism were found between VPA and LTG groups. Furthermore, no differences in menstrual disorders were observed between groups.Conclusions Pubertal girls with epilepsy receiving VPA monotherapy were more likely to develop signs of hyperandrogenism, that is, hirsutism and acanthosis, than those on LEV or controls. However, no differences in occurrence of menstrual disorders and other reproductive dysfunctions were found between VPA, LTG, LEV, and control groups. These findings do not allow us to clearly determine whether or not VPA, LEV, and LTG monotherapies considerably affect reproductive endocrine health in pubertal girls with epilepsy. Therefore, further prospective studies of larger sample sizes are needed to establish if screening tests should be recommended.
Keywords: AED; pubertal females; hyperandrogenism; reproductive endocrine dysfunctions